Anti-Aβ autoantibodies in amyloid related imaging abnormalities (ARIA): candidate biomarker for immunotherapy in Alzheimer’s disease and cerebral amyloid angiopathy. - DiFrancesco, Jacopo C.; Longoni, Martina; Piazza, Fabrizio (Frontiers in Neurology, 2015)
Amyloid Related Imaging Abnormalities (ARIA) represent the major severe side effect of amyloid-beta (Aβ) immunotherapy for Alzheimer’s disease (AD). Early biomarkers of ARIA represent an important challenge to ensure safe and beneficial effects of immunotherapies, given that different promising clinical trials in prodromal and subjects at risk for AD are underway. The recent demonstration that cerebrospinal fluid (CSF) anti-Aβ autoantibodies play a key role in the development of the ARIA-like events characterizing cerebral amyloid angiopathy-related inflammation generated great interest in the field of immunotherapy. Herein, we critically review the growing body of evidence supporting the monitoring of CSF anti-A autoantibody as a promising candidate biomarker for ARIA in clinical trials.